PEDAGOGICAL BASIS OF DEVELOPING COMMUNICATION SKILLS IN PRIMARY STUDENTS - Abdiyeva , Koysintosh; Jovliyeva , Dilshoda (WORLD INTERNATIONAL CONFERENCE ON SCIENCE, TECHNOLOGY AND EDUCATION, 2026)
this article discusses the theoretical and practical foundations of developing communication skills in primary school students. The role of communication in personal development, the factors of forming communicative competence, effective methods used in the lesson process, and the importance of teacher-parent cooperation are analyzed. The research used pedagogical observation, analysis, and generalization methods. The results show that interactive methods, game technologies, and a positive psychological environment are important factors in developing communication skills.